The impacts of weak links on topology discovery process in large-scale wireless multi-hop networks. (November 2020) - Wenxing, Liao; Xiaofei, Shi; Xinying, Chen
In wireless multi-hop networks, especially large-scale wireless multi-hop networks, obtaining the network topology is of vital significance. In fact, in both proactive and reactive routing protocols, before establishing an appropriate end-to-end route, the source node needs to obtain the global or local topology. Our previous research has studied the impacts of weak links on reactive routing protocols, which can also be considered as local topology discovery process. In this article, in order to get insight of the impacts of weak links on topology discovery process, especially the global topology discovery on which the proactive routing protocols rely, we apply a Markov chain to model the most common used topology discovery process in large-scale wireless multi-hop networks. Considering the fading characteristics of wireless channel, we analyze the impacts of weak links on topology discovery algorithms. Simulation and theoretical results show that, with the increase in the network scale, the weak links have great impacts on the stability and even on the feasibility of wireless multi-hop networks.